Sustainable asset integrity management: Strategic imperatives for economic renewable energy generation - Ossai, Chinedu; Boswell, Brian; Davies, Ian (Elsevier, 2014)
This paper develops a framework for sustainable asset integrity management (AIM) with regards to renewable energy generation plants. The authors conclude that increased downtime, low energy output, high cost of maintenance and repair operations, which are attributable to poor assets integrity management, can be mitigated with sustainable AIM. The enhancement of economic and efficient energy generation in renewable energy plants, therefore, involves a structured procedure that combines socio-economic and environmental demands in decision supports for facilities management. This can be achieved utilizing a function interfaced organizational model and techniques that include mitigation, prevention and regulatory programmes. Environmental conscious planning, review and task execution in AIM are vital to health, safety and environmental conservation whilst improved asset lifecycle performance can be reached through competence, compliance, control, communication and co-operation of management and personnel. In conclusion, proper coordination of AIM through an accurate understanding of the stakeholder demands results in efficient renewable energy generation.